(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To describe the current situation of hypertension patient management and treatment at commune health stations in Bat Xat district, Lao Cai province, in 2020. Subjects and Methods: A descriptive cross-sectional study was conducted, retrospectively reviewing 510 records/patient files of hypertension patients undergoing treatment at 20 commune health stations, while also collecting secondary data related to hypertension management and treatment activities in Bat Xat district from June 2019 to September 2020. Results: The study highlighted several strengths in hypertension (HTN) management at commune health stations, with 100% of stations having sufficient medical staff and equipment, as well as 100% of staff being trained and patient records being established. However, the stations still face significant challenges such as a shortage of essential medicines and operational funding. Although the target blood pressure achievement rate was 66.9% for both groups, the HTN detection rate through screening was low, and the establishment of outpatient medical records was limited in the group without WHO support. The results showed that HTN management activities were significantly better in communes with WHO support, while also emphasizing the role of factors such as policies, funding, and organizational models in the effectiveness of disease management. Conclusion: The management of hypertension at commune health stations has strengths in human resources and facilities, but still faces many limitations in funding and medication. The WHO plays a crucial role in ensuring operational effectiveness.